Antecedents of Intention to Use Ride-Sharing Platform - Miharni Tjokrosaputro (Faculty of Economic and Business, 2023)
The Ride-Sharing Platform (RSP) implementation in Indonesia has been emerging recently. The use of this platform is increasing significantly year by year. This study aimed to identify the factors influencing the attitudes and intentions of RSP users in Indonesia. This research discussed the role of customers in service innovation and the relationship between Perceived Usefulness, Perceived Ease-of-Use, Word-of-Mouth (WOM), and Intention to Use RSP from the perspective of TAM and TPB. This research used 208 data originating from 219 samples acquired through questionnaire distribution. The obtained data were then analyzed using the SmartPLS Program. This research shows that Perceived Usefulness, Perceived Ease-of-Use, and word of mouth positively affect the Intention to Use RSP mediated by Customer Attitude toward Service Innovation. This research could contribute to the RSP industry and those who want to join RSP as one of the service providers. This study contributes considerably to the breadth and rigor of the RSP literature from the perspectives of TAM and TPB.JEL Classification: M31, M37, L92How to Cite:Tjokrosaputro, M. (2023). Antecedents of Intention to Use Ride-Sharing Platform. Etikonomi, 22(2), 429 – 442. https://doi.org/10.15408/etk.v22i2.26127.